2007
DOI: 10.1136/tc.2007.019976
|View full text |Cite
|
Sign up to set email alerts
|

Minimal dataset for quitlines: a best practice

Abstract: Objectives:This paper discusses the development of a minimal dataset (MDS) for tobacco cessation quitlines across North America. The goal was to create a standardised instrument and protocol that would allow for comparisons and pooling of data across quitlines for evaluation and research purposes. Principles of utilisation focused evaluation were followed to achieve consensus across diverse stakeholder groups in two countries.Methods:The North American Quitline Consortium (NAQC) assembled a working group with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 17 publications
0
36
0
2
Order By: Relevance
“…A live agent then completed a computer-guided brief assessment based on the minimal data set used by the North American Quitline Consortium 19. Participant demographic characteristics were collected and detailed measures of smoking history, current smoking behaviour and the Heaviness of Smoking Index (HSI) 20.…”
Section: Methodsmentioning
confidence: 99%
“…A live agent then completed a computer-guided brief assessment based on the minimal data set used by the North American Quitline Consortium 19. Participant demographic characteristics were collected and detailed measures of smoking history, current smoking behaviour and the Heaviness of Smoking Index (HSI) 20.…”
Section: Methodsmentioning
confidence: 99%
“…Seven-day and 30-day tobacco point-prevalence quit rates were based on a respondent's self-report of being tobaccofree for the last 7 days or more, or 30 days or more at the time of the 7-month survey (18). Abstinence rates were computed by using both the responder and intent-to-treat methodology.…”
Section: Measures and Definition Of Conceptsmentioning
confidence: 99%
“…Age, sex, education, ethnicity, smoking status (daily or occasional), cigarette consumption, quit intentions and the Heaviness of Smoking Index scores were collected at intake for new callers. 20,21 We conducted an environmental scan of Ontario quitline promotion campaigns during the study period and identified the Driven to Quit Challenge as the only province-wide campaign that promoted the quitline. The Driven to Quit Challenge was a media campaign run in February that promotes Smokers' Helpline through a contest offering smokers a chance Other variables that could increase the volume of calls to the quitline included the January effect and tobacco pricing.…”
mentioning
confidence: 99%